Enteric adenoviruses - Albert, M. J. (Arch Virol, 1986)
In 1978, the World Health Organisation initiated a programme for global prevention and control of childhood diarrhoeas. As a result, the relative importance of various pathogens in the aetiology of diarrhoea in many parts of the world has been recognised. Rotavirus, which ranks as the most prevalent viral pathogen in childhood diarrhoea may be closer to control as many vaccines are in sight. This has been made possible due to a decade of intense research since its discovery. E Ad, which probably ranks as the second most important viral pathogen has not received much attention. As has been discussed, much information has to be gathered about this virus, before W.H.O's. goal of controlling childhood diarrhoea is realised.